2022
DOI: 10.3390/healthcare10091666
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Post-COVID-19 Patients after Hospitalization

Abstract: The COVID-19 pandemic has had a strong impact on people's quality of life (QoL), which is affected by social and economic changes as well as by mental and physical health. The aim of this study was to determine QoL in post-COVID-19 patients who had required hospitalization, and to identify relevant sociodemographic data. We used questionnaires which considered demographic and socioeconomic data, health and vaccination status, the pandemic situation, and EQ-5D scoring. The interactions of all data and the score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
1
1
0
1
Order By: Relevance
“…There appears to be a heightened susceptibility of women to the enduring consequences of COVID-19. This susceptibility aligns with the observed lower immune response in women to milder forms of COVID-19 when compared to men, who tend to experience more severe clinical outcomes directly correlated with a robust immune response [28]. The term "quality of life" is elucidated as the 'subjective well-being' or 'the state of being satisfied with one's own life.'…”
Section: Discussionsupporting
confidence: 59%
“…There appears to be a heightened susceptibility of women to the enduring consequences of COVID-19. This susceptibility aligns with the observed lower immune response in women to milder forms of COVID-19 when compared to men, who tend to experience more severe clinical outcomes directly correlated with a robust immune response [28]. The term "quality of life" is elucidated as the 'subjective well-being' or 'the state of being satisfied with one's own life.'…”
Section: Discussionsupporting
confidence: 59%
“…Considerando essas evidências e a possibilidade do uso das PICS, nota-se a importância da implementação dessas práticas em contextos de saúde [24,25], especialmente em épocas tão desgastantes como a vivenciada com a pandemia e em tempos pós pandemia, nas sequelas dos sobreviventes de COVID-19. A busca por diferentes estratégias que sejam capazes de amenizar os efeitos das mesmas são de fundamental importância, especialmente para melhora da QV e do estado emocional [22,23]. No entanto, muitos desafios se colocam no caminho quando se aborda as PICS seja aqueles relacionados aos entraves em virtude da escassez de publicações e pela influência de concepções enraizadas em relação à medicina alopática como a única forma de tratamento de doenças [10,24].…”
Section: Resultsunclassified
“…Our study revealed that the majority of healthcare workers were women (86%). Some studies have reported that patients after COVID-19 infection develop a poorer QoL, women tend to experience frequent anxiety, and develop severe anxiety symptoms early after discharge [23][24][25]. Some studies have proposed mechanisms to explain the association between certain risk factors, one of which, the female gender has been postulated that hormones may have been involved in persisting the hyperinflammatory status of the COVID-19 acute phase even after recovery [26][27][28].…”
Section: Discussionmentioning
confidence: 99%